Site-specific phosphorylation dynamics of the nuclear proteome during the DNA damage response - Bennetzen, M.V; Larsen, D.H; Bunkenborg, J; Bártek, Jiří; Lukáš, Jiří; Andersen, J.S (Molecular and cellular proteomics, 2010)
To investigate the temporal regulation of the DNA damage response, we applied quantitative mass spectrometry-based proteomics to measure site-specific phosphorylation changes of nuclear proteins after ionizing radiation. We profiled 5204 phosphorylation sites at five time points following DNA damage of which 594 sites on 209 proteins were observed to be regulated more than 2-fold. Of the 594 sites, 372 are novel phosphorylation sites primarily of nuclear origin. The 594 sites could be classified to distinct temporal profiles. Sites regulated shortly after radiation were enriched in the ataxia telangiectasia mutated (ATM) kinase SQ consensus sequence motif and a novel SXXQ motif. Importantly, in addition to induced phosphorylation, we identified a considerable group of sites that undergo DNA damage-induced dephosphorylation. Together, our data extend the number of known phosphorylation sites regulated by DNA damage, provides so far unprecedented temporal dissection of DNA damage-modified phosphorylation events, and elucidate the cross-talk between different types of post-translational modifications in the dynamic regulation of a multifaceted DNA damage response.
Keywords: Amino Acid Motifs; poškození DNA; Cell Line; Cluster Analysis; Cell Nucleus; DNA Damage; Consensus Sequence; posttranslační úpravy proteinů; fosforylace; proteom; aminokyselinové motivy; signální transdukce; Phosphorylation; molekulární sekvence - údaje; shluková analýza; proteinkinasy; Amino Acid Sequence; jaderné proteiny; buněčné jádro; Protein Processing, Post-Translational; reprodukovatelnost výsledků; Chromatography; Signal Transduction; Reproducibility of Results; Time Factors; Protein Kinases; lidé; konsenzuální sekvence; Humans; časové faktory; sekvence aminokyselin; buněčné linie; Molecular Sequence Data; chromatografie; Proteome; Nuclear Proteins